(untitled) (Teología, 2019)
This text corresponds to the presentation of Christoph Theobald to a group of professors of Theology, members of the Argentine Society of Theology. It proposes pastoral destination or pastorality as a key to a transformation of theological work. This puts him before the requirement to think about the cultural diversifications we face and finally redefine theology as the “cultural laboratory” of the Church.